PENGARUH MODEL PEMBELAJARAN BERBASIS LINGKUNGAN TERHADAP KEMAMPUAN NUMERASI DAN WELL-BEING SISWA SEKOLAH DASAR - Seliyanti; Nurul Husna; Insan Suwanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the difference in numeracy ability of students who apply the environment-based learning model and students who apply the direct learning model, determine the influence of environment-based learning models on numeracy and well-being skills, and determine the influence of well-being on the numeracy ability of grade V students of SDN 89 Singkawang. This study uses a quantitative approach with a quasi experimental method and a Nonequivalent Posttest Only Control Group Design. The population in this study is all grade V students of SDN 89 Singkawang with a sampling technique using saturated sampling. The research sample consisted of 49 students, namely 25 students in the experimental class and 24 students in the control class. The data collection technique uses a numeracy ability test and a well-being questionnaire. Data analysis was performed using the Mann-Whitney U test, Effect Size, and simple linear regression. The results showed that the numeracy ability of students who received environment-based learning was better than students who received direct learning, with the results of the Mann-Whitney test of 2.97 > 1.96. The environment-based learning model has a high influence on numeracy and well-being skills with an Effect Size value of 0.8015. Meanwhile, the results of a simple linear regression test showed that well-being did not have a significant effect on students' numeracy skills, with a Fcal value of 0.459 < Ftable 4.28. Thus, the environment-based learning model has a high effect on students' numeracy ability and well-being, but well-being does not have a significant influence on the numeracy ability of grade V students of SDN 89 Singkawang.